Development of physicochemical properties and color of Arbutus unedo L. fruit during osmotic process - Refas, Ibtissem; Amiali, Malek; Belkhir, Safia (Journal of Agriculture and Applied Biology, 2025)
Arbutus unedo L. fruit, rich in bioactive compounds with health bene-fits, experiences rapid softening and significant postharvest quality changes, affecting its consumer appeal and storage life. This study investigates the effect of osmotic dehydration (OD) on the physico-chemical composition, water loss (WL), sugar gain (SG), weight re-duction (WR) and color during drying. The fruit was subjected to OD using sucrose solutions of varying concentrations (30, 50, and 60 °Brix) and temperatures (30 and 40 °C). The fresh fruit exhibited a moisture content of 57 %, a pH of 4.37, and 16.90 % of total soluble solids (TSS). The total phenolic content of arbutus fruit was 15.62 ± 0.78 µg/mg extract and the total flavonoid content was 1.63 ± 0.06 µg/mg extract. Our findings revealed that OD at 30 °Brix enhanced the color and reduced the browning compared to untreated fruit (p < 0.05). OD using a 60 °Brix solution notably reduced the moisture con-tent by approximately 13% while simultaneously lowering the pH and increasing the TSS significantly (p < 0.05). These changes strong-ly correlated with WL, SG and sucrose concentration (R = 0.89, 0.79, and 0.82, respectively). OD prevented the color deterioration during drying with E ranging between 6.43 ± 3.37 and 19.97 ± 3.52. The study proposes that OD at 60 °Brix and 40 °C produces dried arbutus unedo fruit with reduced moisture content and minimized color dete-rioration after the application of convective drying, rendering it suit-able for industrial applications as functional food and the production of value-added dried berries.